THE SIGNIFICANCE OF MATHEMATICAL KNOWLEDGE IN SOLVING PROBLEMS IN BIOLOGY - Khalilova Barnogul Abdulazizovna; Kadyrova Dilshodakhon; Tuychiyeva Khilola Zokirjon kizi (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The article deals with the problems of improving the quality of mathematical knowledge in solving problems in biology, their solutions and prospects, including the improvement of curricula, the design of training, in accordance with the requirements of the time, the use and development of operations of logical thinking, etc.